Біодеградація вуглеводнів нафти дріжджами роду Candida - Русин, І. Б.; Мороз, О. М.; Карабин, В. В.; Кулачковський, О. Р.; Гудзь, С. П.; Rusyn, I. B.; Moroz, O. M.; Karabyn, V. V.; Kulachkovsky, O. R.; Gudz, S. P. (Національний аграрний університет, 2003)
Capability of 14 yeast species to utilize oil hydrocarbons has been analyzed. All strains utilized oil hydrocarbons as a single carbon source. Four strains-destructors that are characterized by higher growth in the presence oil in cultivation medium have been chosen among them. Peroxisomes participation in utilization of oil hydrocarbons by strains-destructors has been shown. Availability of peroxisome key enzymes are characteristic of these strains grown in cultivation medium with oil. Numerous peroxisomes available in the cells of some strains grown in oil cultivation medium have been demonstrated. Utilization of a wide spectrum of oil hydrocarbons has been revealed in all four strains. Two strains are promising to be used for environment purification from oil pollution.
Biodegradation of oil hydrocarbons by Candida yeast
Keywords: дріжджі; пероксисоми; вуглеводні нафти; yeast; peroхisomes; oil hydrocarbons; 556.31 + 57: 012.4 + 017.7 + 052 + 086.3 + 577. 121